Impact of Intervention on Students’ Mastery Level and Analysis of Misconceptions in Operations on Integers - Harun, Nurul Ain; Cuevas, Kyrille Grace; Sagdi, Lorence James; Sapilin, Ailinda; Nasilon, Nurmina; Kadil, Misra; ALVIAR, JAYSON; SOLON, LEO JAY (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
One of the fundamental mathematics concepts expected of a high school student to master is integers. However, many students exhibit misconceptions in operating integers which affect their performance as they advanced to the higher level of mathematics. The purpose of this study is to determine the impact of the intervention on students’ mastery level and analyze the misconceptions in operations on integers. In this study, a quasi-experimental one-group pretest-post-test design was employed. A total of fifty-six (56) grade 7 students were conveniently chosen of which twenty-six (26) were males and thirty (30) were females. Among these, twenty-nine (29) students belonged to Grade 7A, and twenty-seven (27) students belonged to Grade 7B. The data collected were analyzed using JAMOVI, an open statistical software. The Mean Percentage Score (MPS) was calculated to determine the mastery level exhibited by the students. Results revealed significant increase in the mastery level of grade 7 students after the intervention. In addition, there were no significant differences in the mastery level of the students in terms of the gender and section. Although the mastery level of the students improved, there were recurring misconceptions observed after the intervention. The researchers suggest further study evaluating the benefits of intervention in addressing the students' misconceptions in the four fundamental operations on integers.